(untitled) (Journal of the College of Basic Education, 2023)
The aim of this work is to study the effect of GAMMA rays on some rheological and optical properties of Polycarbonate solution in chloroform at different concentrations before and after radiation with source for a rate of 508 (Rad/min) for 40 minutes. Some types of viscosities, optical absorption , refractive index, average viscosity molecular weight, Effective molecular radius, Reflectivity, Coefficient of finesse, Specific reflectance . The results show that most measured and calculated properties increase with concentration in solvent, but the values of density, shear viscosity, relative, specific, reduced, intrinsic and molecular weight increase with radiation and the values of absorbance, refractive index and coefficient of finesse decrease with radiation, this could attributed to degradation leads gasses products .